Severe primary graft failure: Are there lasting impacts? Analysis from the PHTS Database - Jennifer Conway, MD; Tara Pidborochynski, MSc; James K. Kirklin, MD; Ryan Cantor, PhD; Hong Zhao, PhD; Aryaz Sheybani, MD; Jacqueline Lamour, MD; Lakshmi Gokanapudy Hahn, MD; Leslie Collins, MD; Jessica Laks, MD; Darren H. Freed, MD, PhD (JHLT Open)
Background: Primary graft failure (PGF) is a leading cause of early morbidity and mortality after heart transplantation (HTx). PGF is secondary to graft ischemia and ischemia-reperfusion injuries to the cardiomyocytes and vasculature of the donor heart after transplantation. Longer-term outcomes after PGF are not well studied. Methods: Patients with an HTx (January 1, 2010 to June 30, 2022) were identified using the Pediatric Heart Transplant Society registry. PGF was defined as death, retransplantation, or need for mechanical circulatory support within 72 hours of HTx. Kaplan-Meier analysis and Cox proportional hazard modeling were utilized. Results: Of the 4,982 patients with a primary HTx, 5.4% (n = 269) met criteria for PGF. Patients with PGF were younger, with higher proportion of congenital heart disease, longer cardiopulmonary bypass and ischemic times (IT), and more likely to be on extracorporeal membrane oxygenation or ventilator at HTx (all p < 0.0001, IT p = 0.0006). PGF resulted in lower overall survival (1 year: 54% vs 94%, p < 0.001). This remained true when conditional survival was examined at 30 and 90 days but not at 1 year (p = 0.1143). Freedom from rejection did not differ between the groups at overall or conditional on 30 days but was slightly higher for those with PGF at 90 and 365 days. There was no difference in freedom from coronary allograft vasculopathy (CAV). PGF was an independent predictor of overall graft loss (hazard ratios [HR] 4.7, p < 0.0001) and conditional survival to 30 days (HR 2.47, p < 0.0001) and 90 days (HR 1.6, p = 0.012) but not beyond 1 year. Conclusions: Severe PGF is an independent predictor of early mortality post-HTx but subsequently does not further impact long-term survival, overall risk of rejection, or CAV. Understanding the impact of milder forms of PGF on survival and long-term outcomes is still needed. Methods to decrease the risk of PGF, such as alternative preservation and storage techniques, may impact early mortality post-HTx.